2006
DOI: 10.1111/j.1365-3156.2006.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trends for human plague in Madagascar during the second half of the 20th century: a survey of 20 900 notified cases

Abstract: Summaryobjectives To describe the principal characteristics and epidemiological trends for human plague in modern times based on the largest reported series of cases from the highly active Malagasy focus.methods We used a file of 20 900 notified cases of suspected plague, 4473 of which were confirmed or probable, to carry out a statistical analysis of incidence and mortality rates and associated factors for 5-year periods from 1957 to 2001.results Our analysis of trends showed (1) an increase in the incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 15 publications
5
60
0
1
Order By: Relevance
“…Children, especially those sleeping or playing on the ground, have a much higher level of exposure to the bites of infected fleas [35,36]. Furthermore, since the immune system becomes stronger with age, young children may be less able to defend themselves by developing a semi-immunity against the plague bacterium in endemic areas (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children, especially those sleeping or playing on the ground, have a much higher level of exposure to the bites of infected fleas [35,36]. Furthermore, since the immune system becomes stronger with age, young children may be less able to defend themselves by developing a semi-immunity against the plague bacterium in endemic areas (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since the immune system becomes stronger with age, young children may be less able to defend themselves by developing a semi-immunity against the plague bacterium in endemic areas (i.e. the Malagasy central plateau and Medieval and Modern Europe) [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Plague occurs mainly in highlands in DRC 7 and Uganda, where plague cases were more common at > 1,300 m. 13,36 In Madagascar, plague-endemic areas focus on the high plateau of the island. 37 In the western United States, a geographical information system (GIS) -based model indicated that suitability for plague increases for elevations up to 2,129 m but declines at higher elevations. 38 Besides elevation, plague occurrences seem to be linked to seasonal vegetation changes, resulting from rainfall variability through the year, and to moderate EVI values and reasonably high seasonality, suggesting that forests are not suitable for plague; however, because people do not frequently live in the forests, this conclusion could be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…90,108 The high transmission season of the disease to humans has been associated with low abundance of rats and the high chance of accession of fleas to human dwellings. [109][110][111] In the central highlands, most human cases are noted between September and March. This period is characterized by a warmer rainy climate than the low transmission season, which extends from April to August.…”
Section: Lotfymentioning
confidence: 99%
“…135 Onsets of pneumonic plague during such ceremonies have been documented, suggesting that handling of potentially plagueinfected corpses may be the cause. 69,108,111 Thus, the Malagasy Ministry of Health recommended a minimum period of 7 years between death and exhumation of a plague victim, and before any transfer of a corpse from one village to another. 69 Migration and transportation of goods containing infected rats or fleas is another factor favoring rapid transmission of plague in the country.…”
mentioning
confidence: 99%